Using CRISPR/Cas9 genome editing in tomato to create a gibberellin‐responsive dominant dwarf DELLA allele. Issue 1 (22nd June 2018) - Tomlinson, Laurence; Yang, Ying; Emenecker, Ryan; Smoker, Matthew; Taylor, Jodie; Perkins, Sara; Smith, Justine; MacLean, Dan; Olszewski, Neil E.; Jones, Jonathan D. G.
Summary: The tomato PROCERA gene encodes a DELLA protein, and loss‐of‐function mutations derepress growth. We used CRISPR/Cas9 and a single guide RNAs (sgRNA) to target mutations to the PROCERA DELLA domain, and recovered several loss‐of‐function mutations and a dominant dwarf mutation that carries a deletion of one amino acid in the DELLA domain. This is the first report of a dominant dwarf PROCERA allele. This allele retains partial responsiveness to exogenously applied gibberellin. Heterozygotes show an intermediate phenotype at the seedling stage, but adult heterozygotes are as dwarfed as homozygotes.